Education in Rahmatan Lil 'Alamin Perspective - Dian Iskandar Jaelani (Al-Hayat: Journal of Islamic Education, 2017)
Education is believed to be a force and an awareness to make human beings civilized and dignified, which in the Islamic conception of education is aimed at becoming a "grace" for all. To achieve this ideal goal requires a relevant and compatible superstructure and infrastructure for an educational institution, whether formal, informal, and nonformal. In addition, endless endeavors are also indispensable. So far the reality of the output of our educational institution is still far from the ideal ideal. It reads from the alienation of our human education resources when speaking on the global scene as well as grassroots communities, and if examined further and deeper, then many things need to be addressed and rearranged, both in the realm of the system and its implementation. This simple paper will attempt to discuss and provide a concept of locus foothold on the level of Education in the Rahmatan Lil 'Alamin Perspective. Furthermore, this paper is divided into three parts, namely Introduction, Discussion, then end with Closing.